The Effect of Corporate Social Responsibility practices on competitive advantage of media houses in Kenya - Kirima, D. J. N. (Strathmore University, 2025)
This study aimed to examine the effect of CSR practices on the competitive advantage of media houses in Kenya. Specifically, it sought to determine the influence of ethical, economic, philanthropic, and legal responsibility practices on their competitiveness. The study employed a correlational quantitative research design, targeting 488 managerial staff across 122 media houses in Kenya. Respondents were selected through random sampling, and data was collected through structured questionnaires. Analysis involved descriptive statistics, correlation analysis, and multiple regression techniques. This study was underpinned by two complementary theories: Carroll’s Pyramid of Corporate Social Responsibility and Stakeholder Theory. Together, Carroll’s Pyramid defines the nature and scope of CSR activities, while Stakeholder Theory explains how these activities can translate into tangible strategic benefits. They jointly informed the study’s examination of the role of CSR in enhancing the competitive advantage of media houses in Kenya. The findings revealed that ethical and economic responsibility practices significantly contribute to the competitive advantage of media houses, while philanthropic and legal responsibilities did not show a statistically significant effect. The study concluded that CSR practices emphasizing ethics and economic value were more likely to yield competitive benefits in the media landscape, in Kenya. The study recommends that media houses strengthen ethical governance and embed economic responsibility into their core strategic planning. Additionally, integrating innovative CSR models such as cause-related marketing and employee-led community engagement may further reinforce long-term competitiveness. Legal compliance should be supported through continuous training and policy development to enhance sustainability and innovation in the sector.
Full - text thesis